Car Style Recognition 1990-2010 - Abdul Rahman, Julaila; Furuya, Shigeru; Kijima, Akira (2014)
The aim of this research is to identify the user recognition towards the car style in the market line up. To study the car style line up, a certain duration of the period that can show the car style changes need to be observed. It is due to a car style changes happen at least within a year or more. This research will support the designer in their quite long time of design development process. The survey one (I) was done to observe the changes of car form in a series. 155 types of Japanese 2-box car with 248 models, which released in the mass-production from 1990 until 2010, were selected as the samples. Twenty types of ratios based on the car specifications and basic scales were collected and analyzed by Principal Component Analysis (PCA). The result of the survey one (I) showed that the first until seventh components with 76.13 % of cumulative percentage of the total variance explain were taken for further analysis. Twobox car style changes are towards the improvement on efficiency of space usage. The car style is towards cubical, and the A-pillar position is moving to the front of car engine area. Then, the survey two (II) was done to get the user evaluation towards the car style changes. Ten Japanese who are in 20 to 25 years old were chosen as the respondents. Collected data was analyzed by MDS (Multidimensional Scaling) and Cluster analysis. Four kinds of groups were identified, which were ‘long body’, ‘wagon’, ‘high and long body’ and ‘high and box’. The results from both surveys were analyzed in detail. The user recognized the car style direction similar with the actual car style changes in the market line up. The user recognition on the car style has a similar direction towards the actual car style changes that released in the market